2017
DOI: 10.3390/en10111920
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of NaOH-Impregnated Calcined Oyster Shell-Catalyzed Transesterification of Soybean Oil

Abstract: Abstract:The objective of this research is to develop a kinetic model to describe the transesterification of soybean oil with methanol using NaOH-impregnated calcined oyster shell (Na-COS). Batch experiments were performed via a two-factor randomized complete block design using a molar ratio of methanol to oil (MR) of 6, 12, and 18 and catalyst loadings (CL) (mass of catalyst/mass of oil in %) of 2%, 4%, 6%, and 8% to obtain fatty acid methyl ester yields. In addition, the catalyst was studied by X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…This doublet feature indicated that some of the surface oxygen had been shifted to lower BE for both catalysts, when compared to control (calcined oyster shell), acquiring a higher effective negative charge. As was also observed in our recent research [16], the shift in oxygen would have enhanced the electron donating ability, suggesting that the surface oxygen was more basic [30]. As a result, the increased electron donating ability may have allowed triglyceride and methanol to form a tetrahedral intermediate that may have resulted in FAME after structural rearrangement [2].…”
Section: Catalyst Characterizationsupporting
confidence: 77%
See 3 more Smart Citations
“…This doublet feature indicated that some of the surface oxygen had been shifted to lower BE for both catalysts, when compared to control (calcined oyster shell), acquiring a higher effective negative charge. As was also observed in our recent research [16], the shift in oxygen would have enhanced the electron donating ability, suggesting that the surface oxygen was more basic [30]. As a result, the increased electron donating ability may have allowed triglyceride and methanol to form a tetrahedral intermediate that may have resulted in FAME after structural rearrangement [2].…”
Section: Catalyst Characterizationsupporting
confidence: 77%
“…The specific surface area of the catalyst synthesized was determined using Quantachrome Monosorb Surface Area Analyzer (Quantachrome Instruments, Boynton Beach, FL, USA) based on the Brunauer-Emmett-Teller (BET) nitrogen adsorption method [16]. Prior to the measurement, all catalysts were degassed at 120 • C for 8 h.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Biodiesel is commonly produced from edible feedstocks such as soybean, sunflower, and rapeseed oils [5][6][7][8]; however, the use of these feedstocks for biodiesel production is restricted because of their high cost (which accounts for 75% of the production cost) and competition with demand for the food supply [9][10][11]. Therefore, inedible and waste oils have been developed as potential feedstocks for biodiesel production [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%